Cultivation of energy crops by ecological methods under the conditions of global climate and environmental changes with the use of diatom extract as a natural source of chemical compounds - Piotrowski, K.; Romanowska-Duda, Z.; Messyasz, B. (Acta physiologiae plantarum, 2020)
Modern agriculture must be subject to some adaptation processes due to unpredictable climate changes. One of the activities that enables the production of plant biomass in adverse climatic conditions is the development of ecological and innovative crop technologies using natural plant extracts. The elimination of synthetic fertilizers and their replacement with products based on organic matter will increase the plant’s resistance to negative conditions of environmental stress, will have a positive effect on the development and yielding of plants and will reduce cultivation costs. The plant material: willow ( Salix viminalis ), Jerusalem artichoke ( Helianthus tuberosus ) and Virginia mallow ( Sida hermaphrodita ). The natural extract was obtained from Navicula sp. (Bacillariophyceae) monocultures, which was applied to plants in three variants: watering, spraying (foliar application) and watering and spraying. Every 2 weeks: plant height and chlorophyll content index were determined and at the end of the growing season, an analysis was made of: fresh and dry biomass, gas exchange activity in plants (net photosynthesis, transpiration, stomatal conductivity and intercellular CO 2 concentration). The enzymatic activity of acid (pH = 6.0) and alkaline (pH = 7.5) phosphatase, RNase, dehydrogenases, as well as the integrity of cytoplasmic membranes was determined. The obtained results confirmed the positive effect of diatom monoculture extract on the growth and development of the plants. The analyzed physicochemical parameters were characterized by 15–20% higher values in comparison with the control. The use of natural extracts from Navicula sp. can be an alternative to chemical fertilizers and is considered one of the promising strategies in organic agriculture.